Machine Learning in Remote Sensing and GIS: Progress, Applications, and Future Prospects (Prakriti - The International Multidisciplinary Research Journal, 2024)
This research paper explores the intersection of machine learning, remote sensing, and  Geographic Information Systems (GIS) with a focus on state-of-the-art systems, applications,  and future developments. Machine learning techniques have made significant progress in recent  years, enhancing data analysis, classification, and prediction functions to provide better and more  efficient solutions in remote sensing and GIS.
Keywords: Machine Learning; Supervised learning techniques; classification